THE EFFECTIVENESS OF USING YOUTUBE AS A MEDIUM FOR TEACHING EFL IN IMPROVING STUDENTS’ SPEAKING SKILLS: A SYSTEMATIC REVIEW - Amal, Muhammad Ikhlasul; Yamin, Moh.; Rosalina, Elsa (Universitas PGRI Palembang, 2025)
This study presents a systematic review of recent empirical research examining the role of YouTube as an instructional tool for enhancing English as a Foreign Language (EFL) learners' speaking abilities, with particular emphasis on vocabulary development, pronunciation improvement, and confidence building in digital learning contexts. Adhering to the PRISMA 2020 framework, the review analyzed fifteen empirical studies published between 2020 and 2023, sourced from databases such as Google Scholar, ERIC, and DOAJ. The findings indicate that YouTube supports speaking skill development by offering learners authentic, multimodal, and repeated exposure to spoken language. Results showed that learners experienced better vocabulary acquisition, more accurate pronunciation through mimicry, and increased speaking confidence due to the flexibility of self-paced learning. Conversely, unstructured or passive viewing was found to have minimal impact. The implications of this review are significant for EFL educators, curriculum developers, and educational institutions seeking to effectively incorporate YouTube into speaking instruction through interactive, reflective, and task-based approaches. This study offers a distinctive synthesis of recent global research and emphasizes pedagogical techniques that promote active engagement in speaking rather than passive content consumption.